Industry report the problem of sustainable competitive advantage in Philippine call centers - Alava, Aileen S. (2006)
Facing high expectations as the newest "sunshine industry", the call center industry in the Philippines appears to have dimmer prospects in the coming years. Having experienced rapid growth from 2000 to 2003, the industry experienced a slowdown in growth from 2004 to 2006, raising the question of how sustainable the country's competitive advantage is against neighboring competitors such as India and China. This paper uses Porter's Diamond Model to analyze the factors resulting in competitive advantage between nations, and provides industry player and market information on the Philippine call center industry, as well as updates on how the industry's participants are seeking to address the industry's challenges.